TEACHERSâ€™ EFFORT TO DISCIPLINE THEIR STUDENTS IN THE KINDERGARTEN OF TAHFIZH ANAK BANGSA BANDA ACEH - Iqbal, Muhammad (Jurnal Ilmiah Pendidikan Anak (JIPA), 2019)
This research is called â€œTeachersâ€™ Effort to Discipline their Students in the Kindergarten of Tahfizh Anak Bangsa Banda Acehâ€. The formulation of a problem in this research is how efforts to teachers in discipline early childhood in kindergarten Tahfizh Anak Bangsa Banda Aceh. A method of the research is descriptive qualitative. The researchers found that teachers in various methods in discipline eraly childhood the discipline kid came to school timely, smoothing shoes when to the learn, marching made, dressed decorated with, collect and smoothing clothes made, littering in place, was their hands befor and after eating. Methods used by teachers it can to fix discipline attitude for chidrens in kindergarten tahfizh one of the nation. Â Keywords: Teachersâ€™ effort; Discipline; Early Childhood